Analysis of a Contactless ECG Monitoring System. Issue 4 (4th July 2021) - Anurudhya, K.; Mohan, N. Madhu
Abstract : Electrocardiography is one of the vital physiological signals which gives information about the different phases of cardiac activity. Monitoring the activity of the heart plays a major role in timely treatment and thereby reduces the number of deaths due to cardiac diseases. As there are several problems posed by the conventional ECG monitoring system for long term applications, a contactless ECG monitoring system can be used as an alternative. But there are several downsides to contactless ECG monitoring system as well, which prevent it from reaching the standards required for clinical use. Hence, an analysis of the different factors that can possibly affect the quality of the ECG signal being acquired using the contactless system is required, in order to understand the problems better and to overcome them. The different factors that are considered in the present analysis are change in dielectric material, change in thickness of the dielectric, effect of motion artefacts, and effect of stray and cable capacitances.